Advancing teaching excellence in the era of education 5.0: learner-driven pedagogy, technology integration and research-informed practice - Abdillah, Nasirin (Penerbit UiTM (UiTM Press), 2026)
The rapid advancement of Industry 4.0 technologies has reshaped higher education, requiring teaching excellence to be redefined in the era of Education 5.0. This paper explores how Malaysian higher education can advance teaching excellence by embedding learner-centred pedagogy within technology-enhanced learning environments. It analyses how artificial intelligence (AI), big data, gamification and digital platforms enable interactive, personalised, and inclusive learning, while also addressing challenges such as the digital divide, cybersecurity and faculty readiness. The paper further highlights the importance of collaborative and interdisciplinary approaches, supported by academic research and policy frameworks such as the Higher Education Plan 2025–2035 and Education 5.0@UiTM. The findings argue that technology in learning is not merely a tool for content delivery but a transformative enabler of engagement, employability and ethical resilience. By integrating pedagogy, technology and research, higher education institutions can build adaptive ecosystems that prepare graduates for dynamic and uncertain futures.